Anti-Inflammatory Activity of Aqueous Extract of Psychotria Sarmentosa on Acute and Chronic Inflammatory Animal (Wistar Rat) Models - Ratnayake, W.M.K.M.; Chandrika, U.G.; Suresh, T.S.; Abeysekera, A.M.; Salim, N. (Proceedings of 3rd Annual Scientific Conference 2016, Sri Lanka Association for Laboratory Animal Science, 2016)
Attached
Keywords: anti-inflammatory; carrageenan; formaldehyde; paw oedema; Psychotria sarmentosa